Coastal Village Development Strategy Based On The Potential Of Marine Tourism In Analyzing The Suitability Of Beach Tourism In Munjungagung Village, Tegal Regency, Central Java Province - Beni Sabdo Nugroho; Frida Purwanti; Pujiono Wahyu Purnomo; Atrasina Adlina (Ridwan Institute, 2022)
Enough resources that have great potential are coastal resources, but well managed are marine ecotourism resources. In Tegal Regency, a village is well known for its beautiful beaches and never empty of visitors during holidays. The village is Munjungagung Village. In addition to the village which is never deserted, there is also a Fishing and Diving Spot, this can be a potential for marine ecotourism and has a great opportunity to continue to be developed into mainstay tourism, and it is hoped that this potential can improve the welfare of the community. This study aims to analyze the suitability of coastal tourism from the Coastal Village, which was developed based on the potential for marine tourism in Munjungagung Village, Tegal Regency, Central Java Province. The method or technique chosen is the descriptive method. This research has been carried out from April to November 2021 to determine the potential for marine tourism to the tourism suitability index (IKW). The data were analyzed using the formula for calculating the Tourism Suitability Index (IKW). This study showed that the tourist sites in the research area were still suitable for beach tourism activities, snorkeling, and diving. The suitability class for beach tourism and snorkeling and diving has an IKW value of 94.05% and is included in the S1 category (Very Suitable).